ANALISIS YURIDIS PENGAMBILALIHAN SAHAM PT ALFA RETAILINDO Tbk OLEH PT. CARREFOUR INDONESIA Tbk DARI PERSPEKTIF UNDANG-UNDANG NOMOR 5 TAHUN 1999: Studi Kasus Putusan Komisi Pengawas Persaingan Usaha Nomor 9 Tahun 2009 - , yuniyar kristi; , Ninik Darmini, SH, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of research to find and review the rationale used by the Commission to determine that the PT Carrefour Indonesia Tbk has a monopoly , and examines the responsibility of the notary deed takeover of PT Alfa Retailindo Tbk PT Carrefour Indonesia Tbk. Nature of Research and Methods This study is a impiris juridical law , which is based on research conducted with the literature data as the data which is the primary and secondary data in the form of legal materials that had to do with the subject of research supported by the results of the interview . Impiris own research to form evaluative aims to assess the implementation of legislation and carried out by conducting library research and field research . Verdict Research Business Competition Supervisory Commission ( KPPU ) declared that the number 09/KPPU-L/2009 a benchmark to determine PT Carrefour Indonesia has declared a monopoly and violating Article 17 paragraph ( 1 ) of the Monopolies and Article 25 paragraph ( 1 ) a letter of dominant Position of Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition is the relevant market and dominant position after the acquisition . Further benchmarks used by the South Jakarta District Court 1598/Pdt.G/2009/PN.Jkt.Sel dated February 17, 2009 is the relevant market and dominant position . The responsibility of the notary deed takeover of PT Alfa Retailindo Tbk PT Carrefour Indonesia Tbk is made in the authentic act of the Indonesian takeover of PT Alfa Retailindo Tbk PT Carrefour Indonesia Tbk and provide assurances creation date of the deed . This is in accordance with Article 15 paragraph ( 1 ) of Law Number 30 Year 2004 concerning Notary stated that the notary is authorized to make authentic act of all deeds , agreements and provisions that are required by legislation and / or desired by stakeholders .